An Evaluation of Mathematics Intervention Program for Struggling Students Using Provus Discrepancy Evaluation Model: Aligning Design, Implementation, and Student Achievement - Baybayan, Jericho Y. (Transpublika Publisher, 2025)
In helping academically challenged learners, mathematics intervention is important in targeting specific learning gaps with customized instructional strategies. In response to the learning losses caused by the pandemic, DepEd in the Philippines officially launched the National Learning Recovery Program, under which focused intervention in Mathematics, among others, is mandated based on evidence. This study assessed the Mathematics Intervention Program for struggling students in a Central Mindanao school using Provus’ Discrepancy Model of Evaluation. This was in line with the overall objectives of determining the expected student achievement level as defined by the program, analysis of actual student performance before and after intervention, the recognition of discrepancies worth mentioning, and recommendations for improvement of the program. According to the results, 95.2% of students before the intervention were below standard in relation to the DepEd's Most Essential Learning Competencies (MELCs) and DepEd Order No.8, s. 2015. In contrast to pre-test results, which indicated a considerable gap in student performance, the post-intervention performance showed a drastic increase in the number of students who achieved satisfactory to outstanding levels. The mean score increased from 21.32 (pre-test) to 45.31 (post-test), which means students showed increased understanding and fluency in mathematical concepts and procedures. This implies that the program has effectively dealt with the intervening factor standing between the performance of the students and the desirable level. Some recommendations put forth are institutionalizing the program, regular diagnostics, intensive training for teachers in differentiated instruction and formative assessment, improvement of learning resources, and parental involvement.